An Analysis of Genetic Diversity Across the Maize Genome Using Microsatellites - Vigouroux, Yves (Genetics Society of America, 2005)
How domestication bottlenecks and artificial selection shaped the amount and distribution of genetic variation in the genomes of modern crops is poorly understood. We analyzed diversity at 462 simple sequence repeats (SSRs) or microsatellites spread throughout the maize genome and compared the diversity observed at these SSRs in maize to that observed in its wild progenitor, teosinte. The results reveal a modest genome-wide deficit of diversity in maize relative to teosinte. The relative deficit of diversity is less for SSRs with dinucleotide repeat motifs than for SSRs with repeat motifs of more than two nucleotides, suggesting that the former with their higher mutation rate have partially recovered from the domestication bottleneck. We analyzed the relationship between SSR diversity and proximity to QTL for domestication traits and observed no relationship between these factors. However, we did observe a weak, although significant, spatial correlation for diversity statistics among SSRs within 2 cM of one another, suggesting that SSR diversity is weakly patterned across the genome. Twenty-four of 462 SSRs (5%) show some evidence of positive selection in maize under multiple tests. Overall, the pattern of genetic diversity at maize SSRs can be explained largely by a bottleneck effect with a smaller effect from selection.